Direito à saúde e à segurança alimentar: uma análise do Projeto de Lei nº 34/2015 que dispõe sobre rotulagem e rastreabilidade de organismos geneticamente modificados e suas implicações no direito à informação, à segurança alimentar e à saúde - VALE, Karla Cristiane Pereira (2021)
This research addresses the protection of the right to information, food safety and health of the population based on the labeling and traceability of genetically modified organisms present in food. Its main objective is to evaluate the Bill No. 34/2015 and its implications in the construction of Brazilian jurisprudence regarding the right to health, information and food safety of consumers of foods produced from genetically modified organisms. For this purpose, Ulrich Beck's theory of risk was used as a theoretical framework for the research, one of the most important sociological theories of the 20th century, with great impacts on legal and social sciences, which relates modernization as a generalizing concept. From a methodological point of view, based on the deductive method, the proposed study was conducted through a qualitative approach, with a bibliographic, documental and jurisprudential nature, using the technique of content analysis. It was concluded that, due to the emergence of new technologies in the field of genetic engineering and considering the scientific uncertainties about the possible damage to health that genetically modified organisms can cause, it is essential to adopt the precautionary principle, in order to effectuate the preservation of fundamental rights, including information, health and food safety.